Virtual Based Screening of Rosmaniric Acid and Its Derivatives as Potential Anticancer Approach Targeting HIF-1a - Naufal, Achmad Hanif; Wachid, Nisa Nabila Aufa; Kamila, Fairuz Sarah; Wahyuningsih, Nadia; Ilmiyah, Silvi Zakiyatul; Nafisah, Wirdatun; Fatchiyah, Fatchiyah (Universitas Brawijaya, 2025)
Cancer is one of the leading causes of death in the world. Rosmarinic acid becomes one of the important polyphenolic compounds. It includes derivatives of two amino acids, caffeic acid from phenylalanine and 3,4-dihydroxyphenyl-lactic acid from tyrosine, secondary metabolites found in many herbal plants from the subfamily Lamiaceae and Boraginaceae. Rosmarinic acid works in inhibiting the occurrence of metastases and tumor formation. In this study, we evaluated rosmarinic acid and its derivatives through study literature. The compounds were downloaded from the PubChem database, while the three-dimensional structure of HIF-1a was retrieved from RCSB PDB. The biological activity was analyzed using the PASS server, and the cytotoxic effect was predicted using CLC-Pred., The pharmacological properties of bioactive compounds were analyzed using SwissADME. The compounds and HIF-1a were prepared using PyRx 0.8 version and Discovery Studio software, docked specifically using Autodock Vina, visualized using Discovery Studio software, and molecular dynamic simulation using CABS-flex 2.0. Rosmarinic acid and its derivative showed an inhibition with the highest affinity value of compound against HIF-1a are control (-6.9 kcal/mol), Rosmarinic acid (-6.4 kcal /mol), and Methyl rosmarinate (-6.3 kcal/mol). Rosmarinic acid could be expected to have activity as an inhibitor modulated at the post-translational level. Comprehensive and further analysis is required in future research based in vivo and in vitro for the development of cancer treatments.